1996
DOI: 10.1111/j.1432-1033.1996.00431.x
|View full text |Cite
|
Sign up to set email alerts
|

O‐Glycosylated Species of Natural Human Tumor‐Necrosis Factor‐α

Abstract: Tumor-necrosis factor-a, produced by human B-cell lymphoblastoid cell line BALL-I, was expressed as four protein bands on SDS/PAGE analysis. It may have been glycosylated, based on the fact that the heavier two of the four bands disappeared after neuraminidase treatment. Sugar composition analyses revealed that the tumor necrosis factor-a contained galactose, N-acetylgalactosamine and N-acetylneuraminic acid as sugar components. To prepare sugar chains, tumor necrosis factor-a was treated with alkaline borodeu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…N- and O-linked glycosylation are common post-translational modifications that have been described for a variety of ADAM substrates besides the IL-6R, e.g., for TNFα [46] or transforming growth factor alpha (TGFα) [47]. Substrates with and without glycans have also been used to generate novel ADAM17-specific inhibitors [48].…”
Section: Discussionmentioning
confidence: 99%
“…N- and O-linked glycosylation are common post-translational modifications that have been described for a variety of ADAM substrates besides the IL-6R, e.g., for TNFα [46] or transforming growth factor alpha (TGFα) [47]. Substrates with and without glycans have also been used to generate novel ADAM17-specific inhibitors [48].…”
Section: Discussionmentioning
confidence: 99%
“…1, C and D). It has to be noted, however, that posttranslational modifications may be cell lineage specific because O-glycosylation of TNF in the human B cell lymphoblastoid cell line BALL-1 has been reported (29). This might reflect involvement of differential, cell line-specific trafficking mechanisms in delivery of the protein cargo to the target compartment such as mast cell granules or in release to extracellular space.…”
Section: Discussionmentioning
confidence: 99%
“…O-glycosylation has been proposed to specifically affect ADAM-mediated ectodomain shedding (15,16). Tumor necrosis factor alpha (TNF-α), a type 2 transmembrane precursor protein that undergoes ectodomain shedding to produce a soluble truncated form, was shown to be O-glycosylated near a known ADAM cleavage site in lymphoblastic leukemia B cells (16), and Minond and colleagues showed that glycosylation of synthetic peptides covering the TNF-α cleavage site affected in vitro ADAM processing (15).…”
mentioning
confidence: 99%
“…Tumor necrosis factor alpha (TNF-α), a type 2 transmembrane precursor protein that undergoes ectodomain shedding to produce a soluble truncated form, was shown to be O-glycosylated near a known ADAM cleavage site in lymphoblastic leukemia B cells (16), and Minond and colleagues showed that glycosylation of synthetic peptides covering the TNF-α cleavage site affected in vitro ADAM processing (15). Furthermore, it was recently found that also ADAM mediated cleavage of the extracellular N-terminal tail of the GPCR β1-adrenergic receptor may be affected by O-glycosylation (17).…”
mentioning
confidence: 99%